Fertilizer overuse in Chinese smallholders due to lack of fixed inputs. (1st September 2021) - Ren, Chenchen; Jin, Shuqin; Wu, Yiyun; Zhang, Bin; Kanter, David; Wu, Bi; Xi, Xican; Zhang, Xin; Chen, Deli; Xu, Jianming; Gu, Baojing
Abstract: Fertilizer overuse by smallholder farmers is widespread in China, leading to significant financial losses and threatening the environment. Understanding what mechanism behind this is critical for agricultural and environmental sustainability. By using a fixed effect panel model of over 20, 000 rural households in China from 1995 to 2016, we found that the low ratio of fixed inputs such as machinery and knowledge to total inputs is the key factor leading to over-fertilization in smallholder farms. Low fixed input can result in or interact with nutrient-unbalanced fertilization, low agricultural income ratio and more cash crops that further aggravate fertilizer overuse. Smallholders lack fixed inputs, then compensate by over-applying fertilizer to attempt to achieve their yield goals. Thus, improving fixed input via increasing the average farm size to 3.8 ha or advanced service rental could save not only 45% fertilizers but also increase 16% agricultural net profit, benefiting agricultural and environmental sustainability. Highlights: Low fixed input ratio among smallholders leads to fertilizer over-applying. Income ratio, crop type and service rental significantly affect fertilizer overuse. Scale-farming or advanced service rental could sustain agricultural environment. Nutrient-balanced fertilization is normally observed on large farms.